Using the Delphi Method to Improve the Curriculum - Blair, Shirely; Uhl, Norman P. (Canadian Journal of Higher Education, 1993)
An example of employing the Delphi technique for curriculum improvement at a Canadian university is described. This technique was used to identify essential course components to be included in a revised Office Administration program. In addition to providing the necessary information for updating and improving the curriculum, the Delphi technique allowed the department to receive information from and educate guidance counsellors and future employers with regard to the proposed changes in the program. The Delphi technique made it possible to obtain opinions from five diverse groups at relatively low cost and effort. The anonymity that the Delphi method provides helped to ensure that responses reflected accurately the opinions of the respondents. A number of areas of study and special competencies and skills were identified as being essential to a program designed to meet the needs of the automated workplace. The study determined that the program should encompass a much larger component in office technology than existed previously and that the focus of the program should be on information management rather than office administration. Along with the methodology, the advantages and disadvantages of using the Delphi technique for improving the quality of the curriculum are discussed.